Etnomatemática: aproximação da ciência com os saberes locais do cotidiano dos ribeirinhos do alto sertão sergipano - Santos, Jaedson dos (2024)
The search for understanding educational relationships in the context of Mathematics Education Ethics is sometimes complex and requires knowledge of the different coexisting realities, how the ways of teaching and learning of students are constructed, reconstructed and influenced ways that live in the countryside. Likewise, how can we try to break with the paradigm of that mathematical knowledge is something "ready" "finished" and presenting Mathematics as a living science, as in fact it is. In this sense, our objective is to understand mathematical knowledge constructed empirically by masters when building a boat, whether for day-to-day fishing, or for sailing competitions and knowledge and techniques involved in making fishing gear (net, cast net and pit) in order to take them as inspiration for school mathematics teaching practices. To this end, semi-structured interviews were used and direct observation of activities was carried out. sociocultural activities such as the production process of nets and nets; construction of vessels, both for fishing and sailing races, as well as boat competitions. sailing along the Alto Sertão Sergipano. The data obtained were analyzed under light of Ethnomathematics, the mobilization of Cognitive Processes and Cognitive Education, based on authors such as D’Ambrosio (1990), D’Ambrosio (1996), Fossa (2022), Pistrak (1981), Knijnik (2019), Minlton Rosa (2022), Bassanezi (2002) and Freire (1996), the which indicate the need for reflection on the teaching-learning process, a since, in the context of rural education, it is unfeasible to think about education, in a ticular in mathematics education, without taking into account the construction of thought mathematics that occurs in the development of sociocultural activities carried out by subjects in the interactions they carry out in their daily life. In the same sense, we suggest that observing the Ethnomathematic ideas developed by these riverside dwellers is inspiring for educators, as they can take into account the cultural universe of their students, making it possible to create a starting point between what students already know and the new ideas that are intended to be developed in the school context.